The impact of neoadjuvant immunotherapy on perioperative outcomes and survival after esophagectomy for esophageal cancerCentral MessagePerspective - Lye-Yeng Wong, MD; Douglas Z. Liou, MD; Leah M. Backhus, MD; Natalie S. Lui, MD; Joseph B. Shrager, MD; Mark F. Berry, MD (JTCVS Open, 2023)
Objective: Immunotherapy for esophageal cancer is relatively novel but increasingly used. This study evaluated the early use of immunotherapy as an adjunct to neoadjuvant chemoradiotherapy before esophagectomy for locally advanced disease. Methods: Perioperative morbidity (composite of mortality, hospitalization ≥21 days, or readmission) and survival of patients with locally advanced (cT3N0M0, cT1-3N + M0) distal esophageal cancer in the National Cancer Database from 2013 to 2020 who underwent neoadjuvant immunotherapy plus chemoradiotherapy or chemoradiotherapy alone followed by esophagectomy were evaluated using logistic regression, Kaplan–Meier curves, Cox proportional hazards methods, and propensity-matched analysis. Results: Immunotherapy was used in 165 (1.6%) of 10,348 patients. Younger age (odds ratio, 0.66; 95% confidence interval, 0.53-0.81; P < .001) predicted immunotherapy use, which slightly delayed time from diagnosis to surgery versus chemoradiation alone (immunotherapy 148 [interquartile range, 128-177] days vs chemoradiation 138 [interquartile range, 120-162] days, P < .001). There were no statistically significant differences between the immunotherapy and chemoradiation groups for the composite major morbidity index (14.5% [24/165] vs 15.6% [1584/10,183], P = .8). Immunotherapy was associated with a significant improvement in median overall survival (69.1 months vs 56.3 months, P = .005) and 3-year overall survival in univariate analysis (65.6% [95% confidence interval, 57.7-74.5] vs 55.0% [53.9-56.1], P = .005), and independently predicted improved survival in multivariable analysis (hazard ratio 0.68 [95% confidence interval, 0.52-0.89], P = .006). Propensity-matched analysis also showed that immunotherapy use was not associated with increased surgical morbidity (P = .5) but was associated with improved survival (P = .047). Conclusions: Neoadjuvant immunotherapy use before esophagectomy for locally advanced esophageal cancer did not lead to worse perioperative outcomes and shows promising results on midterm survival.